Students’ academic burnout during limited face-to-face learning process in Sigi Regency - Silalahi, Micha; Munifah, Munifah; Fitriani, Dian; Hasan, Hasan (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2023)
Academic burnout has emerged as the most commonly reported problem since the Covid-19 pandemic, continuing into the transitional period of limited face-to-face learning during the post-pandemic phase. This study aimed to depict the level academic burnout among junior high school students in Sigi Regency after participating in online learning. For this purpose, a descriptive quantitative survey study was conducted, applying the principles of item total correlation. Out of a total population of 953 students from two schools, 300 students were randomly selected as participants using a simple random sampling technique. The results revealed that students faced difficulties in adapting to the limited face-to-face learning process, which was further exacerbated by challenges in time management and reduced interaction among students due to social restrictions. Students reported experiencing exhaustion due to heavy workload and difficulties in understanding the material, as they were only able to engage in limited offline discussions.